Two Morphological Notes: A Sharp and a Flat - Singh, Rajendra (Revue québécoise de linguistique, 1992)
AbstractThe purpose of this note is to discuss the possibility of relating the lexicon as a unique address and eliminating exceptionality from morphology, both somewhat threatened by some current proposals.